2008
DOI: 10.1186/1742-4690-5-76
|View full text |Cite
|
Sign up to set email alerts
|

The HTLV-1 Tax interactome

Abstract: The Tax1 oncoprotein encoded by Human T-lymphotropic virus type I is a major determinant of viral persistence and pathogenesis. Tax1 affects a wide variety of cellular signalling pathways leading to transcriptional activation, proliferation and ultimately transformation. To carry out these functions, Tax1 interacts with and modulates activity of a number of cellular proteins. In this review, we summarize the present knowledge of the Tax1 interactome and propose a rationale for the broad range of cellular prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
239
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(250 citation statements)
references
References 303 publications
(385 reference statements)
4
239
1
6
Order By: Relevance
“…Previous study has demonstrated that Tax protein may interact with some transcription factors and/or other transcriptional regulators and influence gene expression (Boxus et al, 2008). To elucidate whether Tax inflences HMGB1 expression in the CD4 + T-cells, in the current study, we directly extracted total RNA and protein from Tax + -T cells (TaxP) and Tax --T cells (TaxN) by using RT-PCR, qRT-PCR, and Western blot assays.…”
Section: Tax Protein Enhances Hmgb1 Transcription Levels and Promotesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study has demonstrated that Tax protein may interact with some transcription factors and/or other transcriptional regulators and influence gene expression (Boxus et al, 2008). To elucidate whether Tax inflences HMGB1 expression in the CD4 + T-cells, in the current study, we directly extracted total RNA and protein from Tax + -T cells (TaxP) and Tax --T cells (TaxN) by using RT-PCR, qRT-PCR, and Western blot assays.…”
Section: Tax Protein Enhances Hmgb1 Transcription Levels and Promotesmentioning
confidence: 99%
“…Oncoprotein Tax exhibits diverse functions in host cells, resulting in persistent activation of NF-κB and deregulation of its responsive gene expressions for T cell survival (Patrick et al, 2001;Easley et al, 2010;Alfonso et al, 2012). Tax protein predominantly localizes to the nucleus, However, Tax alone does not bind DNA; moreover, it functions as a transcriptional activator through interactions between the Tax and a large array of transcriptional regulators to regulate cellular processes (Boxus et al, 2008). Notably, the viral-transforming protein Tax is an important part of the oncogenic mechanism of HTLV-I in enhancing transcription by interacting with transcriptional factors.…”
Section: Introductionmentioning
confidence: 99%
“…To override regulatory functions of hDLG, TAX induces its hyperphosphorylation (Boxus et al, 2008). It is noteworthy that TAX mutants lacking the PBM are also impaired in immortalisation and transformation in vitro and in vivo (Xie et al, 2006).…”
Section: Taxmentioning
confidence: 99%
“…The oncogenic potential of TAX is supported by its ability to immortalise cells in vitro, stimulate colony formation in soft agar and produce tumours in transgenic mouse models. Within the cell, TAX exerts its functions by complex formation with more than a hundred cellular proteins (Boxus et al, 2008). We recently proposed that the intrinsically disordered structure of TAX allows a wide variety of conformational changes enabling binding diversity and recognition of differently shaped protein partners.…”
Section: Taxmentioning
confidence: 99%
See 1 more Smart Citation